1988
DOI: 10.1001/archotol.1988.01860180054029
|View full text |Cite
|
Sign up to set email alerts
|

Postirradiation Sarcoma in Retinoblastoma: Induction or Predisposition?

Abstract: \s=b\An alarmingly high rate of postirradiation sarcomas following treatment for retinoblastoma has been described in the literature. We present four new cases and report 57 others from the English literature. Osteogenic sarcoma was the predominant histologic type (58%), followed by fibrosarcoma (21%) and various other sarcomas (21%). The average latency period between irradiation and development of the second primary (sarcoma) was 12.4 years. Irrespective of irradiation, a genetic linkage between retinoblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The reported risk varies widely, but a cumulative incidence of 1% for each year of life has been suggested as an approximate estimate. Earlier reports indicated that many of these malignancies are radiation or chemotherapy induced [43][44][45][46]. However, more recent studies [46][47][48][49] suggest that the development of second primary neoplasms in patients with hereditary retinoblastoma results partly from a genetic predisposition and partly from the potentiating effect of radiotherapy on tumorigenesis through mutation of the second Rb gene (RB1) allele, the first RB1 allele being mutated in all patients with hereditary retinoblastoma [50].…”
Section: Tumor Suppressor and Oncogenic Pathway In Ut-lmsmentioning
confidence: 99%
“…The reported risk varies widely, but a cumulative incidence of 1% for each year of life has been suggested as an approximate estimate. Earlier reports indicated that many of these malignancies are radiation or chemotherapy induced [43][44][45][46]. However, more recent studies [46][47][48][49] suggest that the development of second primary neoplasms in patients with hereditary retinoblastoma results partly from a genetic predisposition and partly from the potentiating effect of radiotherapy on tumorigenesis through mutation of the second Rb gene (RB1) allele, the first RB1 allele being mutated in all patients with hereditary retinoblastoma [50].…”
Section: Tumor Suppressor and Oncogenic Pathway In Ut-lmsmentioning
confidence: 99%
“…Guadagnolo and colleagues noted that the vast majority of HN osteosarcomas arise in either the mandible or maxillary bone [8,9] with 85% of cases involving mandible and maxilla (45% mandible and 40% maxilla) [8,10]. A small number of patients present a history of previous radiotherapy (RT), with consequent osteosarcoma, which was likely radiation-induced [3,[11][12][13]. These tumors and the ones arising de novo seem to have similar histopathology, appearance and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 68% of the children treated with therapeutic irradiation for retinoblastoma, a malignant tumor of the retina, develop bone and soft-tissue sarcomas, with 75% occurring within the irradiated ®eld (Meadows et al 1985). Although osteosarcoma is the predominant tumor histology, these individuals often develop rhabdomyosar-comas arising from the orbital or temporal musculature (Meadows et al 1977;Hawkins et al 1987;Schwartz et al 1988;Hasegawa et al 1998). Radiation-induced secondary tumors in retinoblastoma survivors tend to be more aggressive (Meadows et al 1985), and these individuals tend to do poorly as compared to others with sporadic origin of these tumors.…”
Section: Introductionmentioning
confidence: 99%